Maximum walking speeds obtained using treadmill and overground robot system in persons with post-stroke hemiplegia - Capó-Lugo Carmen E (Journal of NeuroEngineering and Rehabilitation, 2012)
Abstract Background Previous studies demonstrated that stroke survivors have a limited capacity to increase their walking speeds beyond their self-selected maximum walking speed (SMWS). The purpose of this study was to determine the capacity of stroke survivors to reach faster speeds than their SMWS while walking on a treadmill belt or while being pushed by a robotic system (i.e. “push mode”). Methods Eighteen chronic stroke survivors with hemiplegia were involved in the study. We calculated their self-selected comfortable walking speed (SCWS) and SMWS overground using a 5-meter walk test (5-MWT). Then, they were exposed to walking at increased speeds, on a treadmill and while in “push mode” in an overground robotic device, the KineAssist, until they were tested at a speed that they could not sustain without losing balance. We recorded the time and number of steps during each trial and calculated gait speed, average cadence and average step length. Results Maximum walking speed in the “push mode” was 13% higher than the maximum walking speed on the treadmill and both were higher (“push mode”: 61%; treadmill: 40%) than the maximum walking speed overground. Subjects achieved these faster speeds by initially increasing both step length and cadence and, once individuals stopped increasing their step length, by only increasing cadence. Conclusions With post-stroke hemiplegia, individuals are able to walk at faster speeds than their SMWS overground, when provided with a safe environment that provides external forces that requires them to attempt dynamic stability maintenance at higher gait speeds. Therefore, this study suggests the possibility that, given the appropriate conditions, people post-stroke can be trained at higher speeds than previously attempted.